Semi-Implantable Bioelectronics - Fang, Jiaru; Huang, Shuang; Liu, Fanmao; He, Gen; Li, Xiangling; Huang, Xinshuo; Chen, Hui‑jiuan; Xie, Xi (Nano-Micro Letters, 2022)
Developing techniques to effectively and real-time monitor and regulate the interior environment of biological objects is significantly important for many biomedical engineering and scientific applications, including drug delivery, electrophysiological recording and regulation of intracellular activities. Semi-implantable bioelectronics is currently a hot spot in biomedical engineering research area, because it not only meets the increasing technical demands for precise detection or regulation of biological activities, but also provides a desirable platform for externally incorporating complex functionalities and electronic integration. Although there is less definition and summary to distinguish it from the well-reviewed non-invasive bioelectronics and fully implantable bioelectronics, semi-implantable bioelectronics have emerged as highly unique technology to boost the development of biochips and smart wearable device. Here, we reviewed the recent progress in this field and raised the concept of “Semi-implantable bioelectronics”, summarizing the principle and strategies of semi-implantable device for cell applications and in vivo applications, discussing the typical methodologies to access to intracellular environment or in vivo environment, biosafety aspects and typical applications. This review is meaningful for understanding in-depth the design principles, materials fabrication techniques, device integration processes, cell/tissue penetration methodologies, biosafety aspects, and applications strategies that are essential to the development of future minimally invasive bioelectronics. Highlights: 1 Concept of “Semi-implantable Bioelectronics” is raised to cover the major advances and emphasize new insights into building external device. 2 The principle and strategies of semi-implantable device for cell applications are summarized to discuss the typical methodologies to access to intracellular environment by cell penetration and various efficient applications. 3 The principle and strategies of semi-implantable device for in vivo applications are highlighted to discuss the various types of transdermal devices, brain electrodes and microneedle devices for the applications.